Prediction of Performance in a Short Trail Running Race: The Role of Body Composition - Alvero-Cruz, José Ramón; Parent Mathias, Verónica; Garcia Romero, Jerónimo; Carrillo de Albornoz-Gil, Margarita; Benítez-Porres, Javier; Ordoñez, Francisco Javier; Rosemann, Thomas; Nikolaidis, Pantelis T.; Knechtle, Beat (Frontiers in Physiology, 2019)
The aim of the present study was to examine the role of of the classical physiological model of endurance running performance - maximal oxygen uptake (VO2max), %VO2max at ventilatory thresholds (VT), and lactate levels - and body composition on the prediction of short trail running performance. Eleven male trail runners (age 36.1 ± 6.5 years, sport experience 6.6 ± 3.8 years, mean ± standard deviation) were examined for fat mass and skeletal muscle mass, and performed a graded exercise test to measure VO2max, vVO2max and ventilatory thresholds. Also, they participated in a short 27-km trail run with a positive elevation of + 1750 m. Age, years of training and skeletal muscle mass did not correlate with race time (P>0.05). Fat mass and body mass index showed significant correlations with race time (P<0.05). Heart rate, velocity and oxygen consumption at VT1 and VT2 were not significant (P>0.05). Only vVO2max (P=0.005) and VO2max (P=0.007) showed significant correlations. Multiple regression models for VO2max accounted for 57% of the total variance. The vVO2max model variable accounted for 60% and the fat mass model for 59.5%. Finally, the combined VO2max and fat mass model explained 83.9% of the total variance (P<0.05 in all models). The equation for this model is ‘Race time (min) = 203.9956 – 1.9001 * VO2max + 10.2816 * Fat mass %’ (R2 = 0.839, SEE = 11.1 min, P = 0.0007). The multiple regression model that includes VO2max and fat mass percentage most accurately predicted short trail running performance